The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1001/jamainternmed.2017.1309
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dismissal by Primary Care Practices

Abstract: JB. Diagnostic yield of syncope investigation (initiated) in the emergency department: a pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
10
1
Order By: Relevance
“…Many primary care practices, under pressure to implement these guidelines, started discharging patients with chronic pain who were taking opioids (O'Malley et al, 2017). Within 2 years, it was evident that opioid prescriptions were cut by more than one third (Bohnert, Guy, & Losby, 2018); however, opioid overdose deaths reached record high levels (Scholl, Seth, Kariisa, Wilson, & Baldwin, 2018).…”
Section: Shifting Focusmentioning
confidence: 99%
“…Many primary care practices, under pressure to implement these guidelines, started discharging patients with chronic pain who were taking opioids (O'Malley et al, 2017). Within 2 years, it was evident that opioid prescriptions were cut by more than one third (Bohnert, Guy, & Losby, 2018); however, opioid overdose deaths reached record high levels (Scholl, Seth, Kariisa, Wilson, & Baldwin, 2018).…”
Section: Shifting Focusmentioning
confidence: 99%
“…Unfortunately, on occasion, PCPs and clinics who face challenges and strains in patient-provider relationships resort to terminating patients. [5][6][7][8][9] This practice-at times referred to as "firing" patients-is a source of distress for patients, providers, and practices and warrants efforts to better understand and prevent such breakdowns. [10][11][12][13] Given often disruptive and stressful circumstances that patient terminations represent, better understanding their occurrence and causes may prove valuable for mitigating and preventing the harm and friction from which they stem.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] In several previous studies, surveys have been sent to primary care doctors or their practice administrators to explore this topic. [5][6][7][8][9] These surveys reported that patients were most commonly terminated from primary care due to inappropriate, abusive, or threatening behavior. [5][6][7][8][9] The few qualitative studies that have been done have shown that there is often a disconnect between providers' and patients' experiences with the dismissal process and that research is needed to better understand where and how these relationships break down.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent survey of 794 primary care practices, 90% reported discharging patients in the previous two years, often for opioid-related issues. 1 Disruptive or inappropriate behavior was the most common reason for discharge (81%), but 78% reported dismissing patients for violations of a chronic pain or controlled substance agreement. We find this practice worrisome, particularly since many controlled substance agreements use coercive and stigmatizing language that patients may reluctantly sign or have trouble understanding.…”
mentioning
confidence: 99%